KLASIFIKASI PENEMPATAN CALON PESERTA KURSUS DENGAN ALGORITMA NAIVE BAYES - Denny Pribadi; Yusti Farlina; Apip Supiandi (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2018)
The Internet is the easiest means to do online promotion, online buying and testing online. Smartzone Media Studio is a place for courses in architecture. Prospective participants in Smartzone Media Studio must go through the screening step to find out the level of computer knowledge and skills and architectural design. During this time the process is still done manually, that is the prospective participants do the test on the paper, then the results of the answers checked by the examiner, after which the testers calculate the average value to determine at which level the prospective participants will be placed. In order to make the selection process easier and faster, Smartzone Media Studio needs a more effective way, then made a website-based selection system with NaÃ¯ve Bayes algorithm. With this system the assessment and placement of prospective participants is done through the website, so the exam can be done anywhere without having to come to the course. With this system the results of grouping course participants can be more quickly and accurately.